Genome Editing-Based Engineering of CESA3 Dual Cellulose-Inhibitor-Resistant Plants. Issue 2 (25th March 2019) - Hu, Zhubing; Zhang, Teng; Rombaut, Debbie; Decaestecker, Ward; Xing, Aiming; D'Haeyer, Sam; Höfer, Rene; Vercauteren, Ilse; Karimi, Mansour; Jacobs, Thomas; De Veylder, Lieven
Abstract : Functional analysis of a previously identified C17 cellulose-inhibitor-revealed that it operates differently from other known inhibitors, enabling the development of a dual herbicide-resistant line. Abstract: The rapid appearance of herbicide-resistant weeds combined with a lack of novel herbicides being brought to market reduces crop production, thereby threatening food security worldwide. Here, we report on the use of the previously identified cellulose biosynthesis-inhibiting chemical compound C17 as a potential herbicide. Toxicity tests showed that C17 efficiently inhibits the growth of various weeds and widely cultivated dicotyledonous crops, whereas only slight or no growth inhibition was observed for monocotyledonous crops. Surprisingly, when exposed to a mixture of C17 and one of two well-known cellulose biosynthesis inhibitors (CBIs), isoxaben and indaziflam, an additive growth inhibition was observed, demonstrating that C17 has a different mode of action that can be used to sensitize plants toward known CBIs. Moreover, we demonstrate that a C17-resistant CESA3 allele can be used as a positive transformation selection marker and that C17 resistance can be obtained through genome engineering of the wild-type CESA3 allele using clustered regularly interspaced short palindromic repeats-mediated base editing. This editing system allowed us to engineer C17 tolerance in an isoxaben-resistant line, resulting in double herbicide-resistant plants.